Controlled Motivation in Explaining Student Engagement on Adolescents of Authoritarian Parents - Permatasari, Sekarini Andika; Royanto, Lucia R. M. (Universitas Muhammadiyah Surakarta, 2023)
Abstract. Student engagement is considered an important factor for children’s success in academics. Findings in individualist countries showed that authoritative parenting is the best parenting style that promotes positive outcomes, including higher student engagement, while authoritarian parenting impacts negatively. These contrasts with the findings in collectivist countries, which showed that authoritarian parenting could also increase student engagement. This study examines how children raised by authoritarian parents could have high student engagement. Researchers hypothesized that this could happen because authoritarian parenting fosters-controlled motivation in the children. This research is a correlational study to test the role of controlled motivation in mediating the relationship between authoritarian parenting and student engagement. The participants were 460 junior high school students (grades 7-9) from 8 Jakarta, Bekasi, and Tangerang schools. The data were collected online using The Parent as Social Context Questionnaire-Adolescent Report, the Academic Self-Regulation Questionnaire, and the Student Engagement Measurement-MacArthur to assess student’s perception of their parents’ authoritarian parenting, student’s level of controlled motivation and student’s level of student engagement, respectively. Mediation analysis was carried out with PROCESS macro in SPSS v.20. The result shows that authoritarian parenting, as perceived by students, predicts student engagement through controlled motivation. This finding enlightens parents that even resulting in higher student engagement, being authoritarian is better avoided because it elicits an externally regulated motivation, where children act to maintain their ego, avoid punishment, and get external rewards. How authoritarian parenting might impair children in the long-term was discussed.Keywords: authoritarian; controlled motivation; parenting; student engagement